Pembuatan Media Pembelajaran Interaktif Berbasis Articulate Storyline 3 Pada Mata Pelajaran Geometri: Balok, Segi Empat, Kubus dan Persegi Panjang - Fikriyansyah Fikriyansyah; Ummul Khair; Nur Wulan (Universitas Muhammadiyah Enrekang, 2023)
In this day and age computer technology is developing very rapidly, and can be used as a solution to convey or provide information. One of the computer technologies to convey information is interactive learning media. At this time the teacher still has problems adjusting the time and delivery of materials, and also still using blackboards and markers and textbooks in learning. Therefore, the researcher will create interactive learning media based on articulation storyline 3. In the media, articulation storyline 3 is html5 based, which can be run on various devices such as laptops, tablets, and smartphones. The purpose of the researchers in making this research was to help teachers and students in time efficiency in the learning process and to increase students' interest in learning.